EFFECT OF DEVELOPMENT OF DİFFERENT DOSES OF PHOSPHORUS AND SULFUR ON ESSENTİAL OIL AMOUNT AND BİOACTİVE SUBSTANCES IN Lavandula angustifolia (Mill.) PLANT - Gülbeyaz DERIN ALTAY; Sevgi ÇALISKAN (Journal of Animal and Plant Sciences, 2025)
Lavender (Lavandula angustifolia Mill) is a perennial, semi-shrub-like valuable essential oil (EO) plant. There are more than 50 varieties of the Lavandula genus belonging to Lamiaceae family. It is known that phosphorus (P) increases the yield of lavender EO and sulfur (S) is accepted as the fourth main element for plants. This study was conducted to determine the effects of P and S fertilization on the EO amount and bioactive substances of L. angustifolia Mill. (LA). The trial was set up with Sevtapolis variety of LA. Fertilization was applied with triple superphosphate (42-44% P2O5) and 80% elemental liquid S fertilizer before planting the seedlings and the study was conducted for consecutive two years 2022-2023. The P doses were applied as P0: 0 kg P2O5/ha, P60: 60 kg P2O5/ha, P120: 120 kg P2O5/ha, P180: 180 kg P2O5/ha, P240: 240 kg P2O5/ha, and S doses were applied as S0: 0 L S/ha, S30: 30 L S/ha, S60: 60 L S/ha. EO amounts and bioactive substances analyses were performed for each year. In the second year of the experiment, Lavandula EO ratio was found to be 3.37% and EO yield was 37.6 kg/ha. Effective doses for the highest EO yield were calculated as 117.9 kg/ha P and 47.5 kg/ha S, while for the highest antioxidant activity, effective doses were 92.4 kg/ha P and 30.1 kg/ha S. Essential oil amount and Bioactive substances: Linalool, camphor, cis-β-ocimene, trans-β-ocimene, terpinen-4-ol, lavandulyl acetate, lavandulol, 1,8-cineole, limonene, 3-octanone and β-phellandrene ratios of Lavandula EO were found to comply with the International Organization for Standardization and the European Pharmacopoeia standards. Linalyl acetate ratios remained below the desired values in the standards. α-terpineol ratio was measured above the value determined in the standards. The ratios of both components approached the value range specified in the standards in the second year. Although different doses of P application had effect on linalyl acetate and α-terpineol, it did not affect the ratios of other EO components. However, different doses of S applications did not affect the ratios of any component. In crux, it seemed possible to increase EO yield and antioxidant activity of LA without comporomizing oil quality with P and S fertilization.
Keywords: Angustifolia Sevtapolis; amount of essential oil; bioactive substance; Lavender; phosphorus fertilization; sulfur fertilization